Novel techniques in semiconductor characterization and failure analysis using optical feedback laser scanning microscopy - Cemine, Vernon Julius R. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2007)
We have developed an inexpensive and compact Optical Feedback Laser Scanning Microscope (OFLSM) that simultaneously obtains confocal reflectance and current images in a semiconductor sample.